2020
DOI: 10.1080/21623945.2020.1796361
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA response elements regulating expression of CCAAT/enhancer-binding protein (C/EBP) β and δ and MAP kinase-interacting kinases during early adipogenesis

Abstract: Given the high and increasing prevalence of obesity and associated disorders, such as type-2 diabetes, it is important to understand the mechanisms that regulate lipid storage and the differentiation of fat cells, a process termed adipogenesis. Using the well-established mouse 3T3-L1 in vitro model of adipogenesis, we refine how the induction of two key adipogenic transcription factors, CCAAT/enhancer-binding proteins (C/EBPs) β and δ are regulated during early adipogenesis. We identify, in the gene promoters … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…The activation of glucocorticoid receptor signaling by its ligand, dexamethasone, is known to be involved in the activation of adipogenesis through the up-regulation of proadipogenic transcription factors [255]. Specifically, GR activation was shown to be involved in the up-regulation of C/EBPβ [256,257] and C/EBPδ [258] expression with the subsequent induction of C/EBPα. It has been also demonstrated that GR-induced adipogenesis may be mediated by KLF-15-induced PPARγ activation [259].…”
Section: Glucocorticoid Receptormentioning
confidence: 99%
“…The activation of glucocorticoid receptor signaling by its ligand, dexamethasone, is known to be involved in the activation of adipogenesis through the up-regulation of proadipogenic transcription factors [255]. Specifically, GR activation was shown to be involved in the up-regulation of C/EBPβ [256,257] and C/EBPδ [258] expression with the subsequent induction of C/EBPα. It has been also demonstrated that GR-induced adipogenesis may be mediated by KLF-15-induced PPARγ activation [259].…”
Section: Glucocorticoid Receptormentioning
confidence: 99%
“…It has been reported that both C/EBPβ and C/EBPδ were involved in the chondrocyte differentiation, heart development and early regulation of fat formation. [55][56][57] The sub-group III includes C/EBPγ and C/ EBPζ genes, which it has been reported that they are important regulators of cellular stress response networks to maintain the basic life activities of cells. 58 Regulation of gene expression is one of the most important and complex issues in biology.…”
Section: The Expression Pattern and Function Of The C/ebp Gene Family...mentioning
confidence: 99%
“…Overexpression of RUNX2 in non-osteoblastic cells and adipose-tissue-derived MSCs elevates the level of osteoblastic markers, promotes mineralization and inhibits lineage commitment to adipocytes, indicating that a single TF is important for bone development and osteoblast differentiation ( Robert et al, 2020 ). During adipogenesis, the production of cyclic AMP is augmented, resulting in phosphorylation of CREB and an increased expression of CEBPβ ( Merrett et al, 2020 ). CEBPβ, together with the other two CEBP family members (CEBPα and CEBPδ), was reported to be implicated in adipogenic differentiation ( Chen et al, 2016 ; Hu et al, 2018 ; Robert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%